A path to renal transplantation in Nepal (Journal of Pathology of Nepal, 2011)
End Stage Renal Disease affects many people in the world. There are three methods of renal replacement therapy available to patients: Continuous ambulatory peritoneal dialysis, haemodialysis and transplantation. Transplantation is the most viable and cost effective form of renal replacement therapy that is available for these patients. There are 3 factors required to help ensure a successful renal transplantation program: A well legislated donor and recipient program, Human Leukocyte Antigen testing (pre and post transplant), as well as a post transplant follow up program. Keywords: Renal Transplant; South Asia; Nepal; Human Leukocyte Antigen DOI: 10.3126/jpn.v1i1.4453 Journal of Pathology of Nepal (2011) Vol.1, 52-55